Encyclopedia of Polymer Science and Technology 2019
DOI: 10.1002/0471440264.pst130.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Composites: Reinforcing Fillers

Abstract: Addition of reinforcing fillers is a well‐established method to enhance mechanical, electrical, and thermal properties of plastics. Formulation and compounding of polymer matrices with inorganic and organic fillers having peculiar morphology enables the development of new multifunctional materials. Among the physical properties affected by the introduction of fillers in plastics, particular attention has been devoted to the mechanical behavior of the resulting composites. Moreover, introduction of inorganic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 175 publications
0
11
0
Order By: Relevance
“…Fillers are commonly employed to improve or modify various properties of polymer nanocomposite materials. 1–3 Typically, hard fillers such as silica particles, carbon black or graphene-derivatives are added to soft polymer matrices to increase the mechanical strength of the material while maintaining the deformability for various applications such as paints and coatings. 4–6 Although there are various types of fillers available, fillers with high aspect ratio such as carbon nanotubes, glass fibers and cellulose nanofibers have been attracting more interest due to their high reinforcing effect at low filler loading.…”
mentioning
confidence: 99%
“…Fillers are commonly employed to improve or modify various properties of polymer nanocomposite materials. 1–3 Typically, hard fillers such as silica particles, carbon black or graphene-derivatives are added to soft polymer matrices to increase the mechanical strength of the material while maintaining the deformability for various applications such as paints and coatings. 4–6 Although there are various types of fillers available, fillers with high aspect ratio such as carbon nanotubes, glass fibers and cellulose nanofibers have been attracting more interest due to their high reinforcing effect at low filler loading.…”
mentioning
confidence: 99%
“…This behavior could be explained with a better filler-matrix adhesion: in the PP matrix, the good filler matrix adhesion results in a load distribution between slag particles and polymer matrix. Extensive literature demonstrated that composite strength is strongly dependent on the interfacial adhesion between filler and matrix [55][56][57][58][59]. The influence of EAF slag as filler for PP was found to be similar to that of other fillers, such as talc [56,60], and calcium carbonate [61].…”
Section: Mechanical Testsmentioning
confidence: 86%
“…The fundamental properties of rubbery polymers can be improved by blending fillers. Fillers in polymer composites achieve multiple purposes, the most important including reinforcement, improvement in processing, diffusing molecule impermeability, an increase in oil resistance, and a reduction in material cost [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. The rubber industry uses a wide range of fillers because of their merits in rubber compounding.…”
Section: Introductionmentioning
confidence: 99%